Fatigue at time of CIS is an independent predictor of a subsequent diagnosis of multiple sclerosis. Issue 5 (21st July 2014) - Runia, Tessel F; Jafari, Naghmeh; Siepman, Dorine A M; Hintzen, Rogier Q
Abstract : Objective: Fatigue is a common, disabling symptom of multiple sclerosis (MS), but little is known about fatigue in patients with clinically isolated syndrome (CIS), often the presenting symptom of MS. We aimed to investigate the prevalence and severity of fatigue in patients with CIS, and its association with a diagnosis of clinically definite MS (CDMS). Methods: 127 patients were consecutively included in our ongoing prospective CIS study. At baseline, clinical, demographic, laboratory and MRI data were collected, and fatigue severity was assessed using Krupp's Fatigue Severity Scale (FSS); fatigue was defined as FSS≥5.0. Fatigue scores were compared with scores of 113 healthy controls and with scores from the literature. The association of fatigue with CDMS was calculated using Cox regression models. Results: The mean FSS of patients with CIS was 4.3, similar to MS patients, and significantly higher than that of healthy individuals (p<0.001). Fatigue prevalence in patients with CIS (46.5%) was significantly higher than in controls (p<0.001). Fifty-two patients (40.9%) reached CDMS during follow-up. Fatigue was associated with a diagnosis of CDMS in univariate analysis (HR 2.6, 95% CI 1.5 to 4.6) and in multivariate analysis correcting for sex, age, neuroanatomical localisation of CIS, 25-OH-vitamin D, anxiety, depression, MRI dissemination in space and gadolinium enhancement (HR 4.5, 95% CI 1.9 to 10.6). Conclusions: Already at the stage of CIS, fatigue is a very common symptom, with a severity similar to fatigue in MS patients. This fatigue seems unrelated to the type or severity of the attack. Importantly, we found that fatigue was an independent predictor of a subsequent diagnosis of MS.